ANALISIS HUBUNGAN ANTARA PEMBANGUNAN EKONOMI DAERAH, KEBIJAKAN PUBLIK, DAN KESEMPATAN KERJA SEKTORAL DI JAWA TIMUR - Ashar, Khusnul; Supartono, -; Wahyudi, Setyo Tri (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2007)
This research tries to reach 2 points: the relationship between public policy andemployment in East Java, and the contribution to government economic policy inEast Java. The research found that the East Java economic development has beenmore supported by foreign capital then by domestic one. The employment elasticityis high means that capital ploughed in investment created significant inrease inemployment. The leading sectors in East Java economy were Industry, trade andagriculture.Keywords: Public Policy, government policy, Investment, Employment